Prosthodontist contribution in treating post-burn hypertrophic facial scars - Padmanabhan T; Mohmad Kasim; Gupta Rajiv (Wolters Kluwer Medknow Publications, 2010)
The formation of hypertrophic scars is common following healing of the burn wound, particularly in children. The face is one of the areas of the body most frequently affected by burns. Scar formation as a result of burn wounds leads to contraction of the formed granulation tissue, which causes both aesthetic and functional impairment for the patient. Scarring has major psychological and physical repercussions. Scarring on the face and visible regions of the body can be very distressing for the patient. Prevention of scars involves early and continuous use of a compressive orthesis. However, their efficacy is often limited to the facial region because of the contours of this area of body. This paper describes a clinical case of post-burn hypertrophic scars treated with silicone gel sheeting applied with pressure under custom made auto-polymerizing resin stent.